2022
DOI: 10.1111/jfpp.16905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of pineapple peel powder on white finger millet vegan probiotic beverage

Abstract: This study aims to develop, optimize, and evaluate the effective utilization of pineapple peel powder (PPP) in the development of white finger millet probiotic beverages (WFMPBs) using Lactobacillus rhamnosus GG NCDC 347. The optimal condition for the development of PPP incorporated WFMPB was obtained by CCD. The independent variables taken for optimization were inoculum concentration (1–3%), fermentation time (2–8 h), and PPP concentration (1–3%). Viscosity, pH, and probiotic count are taken as response varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…2 C showed the results of DPPH activity (ranging from 11.14 ± 3.56% to 37.05 ± 3.51%) of all the samples fermented by different LAB cultures at varying fermentation times. Our findings are corroborated by Byresh et al (2022) , who observed an increase in antioxidative capability (DPPH) in a probiotic beverage (pineapple peel powder and white finger millet) fermented with L. rhamnosus GG NCDC 347. These results can be linked to a rise in TFC levels.…”
Section: Resultssupporting
confidence: 87%
“…2 C showed the results of DPPH activity (ranging from 11.14 ± 3.56% to 37.05 ± 3.51%) of all the samples fermented by different LAB cultures at varying fermentation times. Our findings are corroborated by Byresh et al (2022) , who observed an increase in antioxidative capability (DPPH) in a probiotic beverage (pineapple peel powder and white finger millet) fermented with L. rhamnosus GG NCDC 347. These results can be linked to a rise in TFC levels.…”
Section: Resultssupporting
confidence: 87%
“…The asymmetric stretching of the C‐H bond was observed in 2922 cm −1 in both CF and T3 but not visible in T6 and T8, instead of that, it was switched to O‐H stretching at 2980 cm −1 , which shows the significant functional group change during high power level MW treatment. In all samples, the peat at 1076 cm −1 , which represents the anhydrides are not changed, and the transmittance at 993 cm −1 (ester group) has significant changes in MW treated samples (Srinivasreddy et al, 2022). A deep characteristics band at 1000–990 cm −1 indicates the α‐1,4 glycosidic linkage and C‐O‐C stretch, in WFMF the transmittance at 1000–900 cm −1 decreased during high‐power MW treatment (Babu et al, 2018).…”
Section: Resultsmentioning
confidence: 98%
“…Fourier‐transform infrared spectra (FTIR) of WFMF were analyzed using the Perkin Elmer (PerkinElmer Spectrum; Model: Spectrum Two), with wavelengths ranging from 400 to 4000 cm −1 at a resolution of 4 cm −1 and 32 scans (Srinivasreddy et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TSS (°Brix), which denotes the % Brix of sugar in aqueous solutions, was measured using a hand‐held refractometer (0–32 °Brix) by sampling 250 μl of the millet beverage (Guney & Gungormusler, 2021) in every 1.5 h interval. Viscosity was determined as described by Byresh et al (2022) using a Brookfield viscometer with an SC4‐18 spindle, which has a viscosity range of 1500–30,000 cP. Initially, the viscometer with SC4‐18 spindle assembly was calibrated using Brookfield's Silicone Viscosity Standard fluids (viscosity values of 9.7 and 97 cP at 25°C).…”
Section: Methodsmentioning
confidence: 99%